Regulatory Requirements of Banks and Arbitrage in the Post-Crisis Federal Funds Market - Garratt, Rod; PRIAZHKINA, SOFIA (Bank of Canada, 2022)
This paper explains the nature of interest rates in the U.S. federal funds market after the 2007-
09 financial crisis. We build a model of the over-the-counter lending market that incorporates
new aspects of the financial system: abundance of liquidity, different regulatory standards for
banks, and arbitrage opportunities created by limited access to the facility granting interest on
excess reserves. The model determines the equilibrium federal funds rate as a function of the
policy rates and explains the “leaky floor” phenomenon in which we observe federal funds rates
that are strictly below the interest rate paid on reserves. Using the model, we explain the impact
of raising government yields and tightening the Liquidity Coverage Ratio (LCR) and the
Supplementary Leverage Ratio (SLR) requirements on the federal funds rates.

Le présent document explique la nature des taux d’intérêt sur le marché des fonds fédéraux
aux États-Unis après la crise financière de 2007-2009. Nous construisons un modèle du marché
hors cote qui intègre de nouveaux aspects du système financier : abondance de liquidités,
normes réglementaires variées applicables aux banques et possibilités d’arbitrage créées par
l’accès limité au mécanisme octroyant des intérêts sur les réserves excédentaires. Le modèle
établit le taux d’équilibre des fonds fédéraux en fonction des taux directeurs et explique le
phénomène du « plancher poreux » qui se caractérise par des taux des fonds fédéraux
strictement inférieurs au taux d’intérêt appliqué sur les réserves. À l’aide du modèle, nous
montrons l’incidence qu’ont sur les taux des fonds fédéraux les hausses de rendement des titres
d’État et le resserrement des exigences de ratio de liquidité à court terme et de ratio de levier
supplémentaire.